Analisis Pola Aktivitas Fisik Selama Ibadah Haji Menggunakan Data Smartwatch Longitudinal: Studi Kasus 784 Hari - Fat'hah Noor Prawita; Dicky Rachmat Iskandar; Riska Ana Gulang (TEMATIK, 2026)
Continuous monitoring using wearable smartwatches enables objective assessment of physical activity patterns in extreme religious activity contexts. This study analyzes 784 days of longitudinal data (February 2024 to April 2026) from an Amazfit T-Rex Pro smartwatch, focusing on the Hajj 1446 H period (17 May to 27 June 2025). The research uses a single-subject case study design involving a healthy 41-year-old male adult. Variables include daily step count, resting heart rate, and sleep duration, analyzed using descriptive statistics, Z-score based anomaly detection (Z > 2.0), and phase comparisons (pre-Hajj, during Hajj, post-Hajj). During Hajj, mean daily steps reached 14,871 steps per day, about twice the pre-Hajj baseline (7,480 steps per day). The core manasik phase (8 to 13 Dhul-Hijjah) showed a mean of 30,840 steps per day, peaking at 42,312 steps on Tasyrik I (11 Dhul-Hijjah), while Wukuf day (9 Dhul-Hijjah) recorded the lowest value of 5,491 steps (Z = -0.38). Resting heart rate remained stable (mean = 62.4 bpm), and sleep duration decreased during the core manasik phase (mean = 4.1 hours). A total of 38 anomaly days were identified, mostly during Hajj, indicating substantial phase dependent physical demands and the potential of wearable data for health monitoring in large-scale religious mass gatherings.